Prevention of Covid 19 in Children in Kupang City : A Holistic Family Role Model - Fransiskus Salesius Onggang; Bringiwatty Batbual; Aben B.Y.H Romana; Blasius Gadur; Emiliandry F.T. Banase (Green Publisher Indonesia, 2022)
Background: COVID-19 is an infectious disease from an infected person carrying the virus to people who are prone contracting it. The role of the family in preventing the spread of the epidemic. Families are at the forefront to break the chain of the spread of the COVID-19 outbreak. Methods: Survey method with a cross-sectional design to identify the relationship between the level of family knowledge and the effectiveness of the covid 19 vaccination. analyzed by looking at the correlation between vaccinations for parents which will have an impact on reducing the rate of transmission in children . Results: Accounting for about 780 children with a percentage of 100%. In the implementation of the prevention of covid 19 there was 355 families with a percentage of 64.50% carried out the implementation of the covid 19 prevention protocol. In the vaccine status of parents, there are still many who have not been vaccinated with 308 families around 56%. Some respondents have a sufficient level of knowledge as much as 51% with a total of 280 families. While the level of knowledge that is the least is at 22.46% with a total of 124 families. Conclusion: The relationship between these factors in the prevention of covid 19 in the city of Kupang is based on children. Based on these results, it can be concluded that there is a significant effect on the level of knowledge on the effectiveness of the covid 19 vaccination at the Kupang City Health Center in 2022, there are still many families who do not know the benefits of the covid 19 vaccination and the effectiveness of the covid 19 vaccine vaccination is still low.